2016
DOI: 10.1080/09593330.2016.1209567
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of upscaling potential of alternative adsorbent materials for highway stormwater treatment in cold climates

Abstract: Generally, studies on alternative adsorbents focus on adsorbent removal capacity, as a function of pollutant concentration, and other practical aspects, such as costs, environmental impact and end of life costs, that can affect the upscaling of adsorbents for real-life applications, are not explicitly considered. Therefore, this study combines multi-criteria modeling with experimental evaluation to integrate both technical and non-technical factors in assessing the upscaling potential of alternative adsorbents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The target metals were added in a quantity to achieve intended concentration of 1 mg/L for each metal in the 1 m 3 influent tank. The reason behind this high concentrations was to be able to obtain detectable concentrations in the outflow and early breakthroughs because high adsorption was expected in the filter based on prior batch tests [17]. The pH of the synthetic stormwater was approx.…”
Section: Column Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…The target metals were added in a quantity to achieve intended concentration of 1 mg/L for each metal in the 1 m 3 influent tank. The reason behind this high concentrations was to be able to obtain detectable concentrations in the outflow and early breakthroughs because high adsorption was expected in the filter based on prior batch tests [17]. The pH of the synthetic stormwater was approx.…”
Section: Column Testsmentioning
confidence: 99%
“…The adsorbents were identified in a previous study, which used multicriteria analysis and batch tests to evaluate the upscaling potential of eight adsorbent materials [17]. In the first phase of the study, the influence of high hydraulic loads as well as deicing salts over the pollutant retention was evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of waste materials is low cost and low need for processing. Factors such as cost, environmental impact, disposal and flexibility of application were taken into account when selecting filter filling materials [9]. When using waste as a filtering material, account is taken of the waste management hierarchy, a waste reduction and reuse strategy is followed that reflects the sustainable management of urban rainwater [10].…”
Section: Introductionmentioning
confidence: 99%
“…The National Public Roads Administrator in Norway had an interest in developing filtration based filters with high hydraulic loading capacity for water quality improvements of road runoff. Through a previously published study [25], two filter media had been identified as promising; granular olivine and pine bark. In addition, activated coal was used as a reference based on its known treatment properties.…”
Section: Introductionmentioning
confidence: 99%